Role of computer simulation to predict the outcome of 3D bioprinting. Issue 2 (April 2017) - Neagu, Adrian
By delivering cells and extracellular matrix one layer at a time, 3D bioprinting enables the fabrication of multicellular structures of precise shape and architecture akin to native tissues. Nevertheless, the technique faces challenges related to the sensitivity and motility of living cells. The final product is not what the printer delivers; the constituent cells rearrange according to mechanisms known from developmental biology. Understanding the postprinting evolution of the bioprinted structure is important for the reliability of the method. This problem is addressed by specifically designed computational models of multicellular self-assembly. The purpose of this review is to present the essence of these models, with emphasis on the underlying assumptions, and to describe their advantages and drawbacks.